Immunogenetic Prediction of VDR Gene SNPs: Lack of Association with Susceptibility to Type 1 Diabetes in Jordanian Patients - Khdair SI; Jarrar YB; Jarrar W (Diabetes, Metabolic Syndrome and Obesity, 2021)
Sawsan I Khdair, Yazun B Jarrar, Wassan Jarrar Department of Pharmacy, Faculty of Pharmacy, Al-Zaytoonah University of Jordan, Amman, 11733, JordanCorrespondence: Sawsan I KhdairDepartment of Pharmacy, Faculty of Pharmacy, Al-Zaytoonah University of Jordan, Amman, 11733, JordanTel +962795513275Email sawsan.khdair@zuj.edu.joPurpose: The interaction of Vitamin D and its receptor plays a crucial role in immune modulation. Therefore, the relationship between the pathogenesis of type 1 diabetes and the genetic variants of Vitamin D receptor, which is involved in the activity of Vitamin D, was studied extensively in different populations. The association of Vitamin D receptor gene polymorphisms with predisposition to type 1 diabetes revealed controversial and inconclusive results. The aim of this study was to examine the association of four Vitamin D receptor polymorphisms with type 1 diabetes in Jordanian patients.Patients and Methods: Analysis of the single nucleotide polymorphisms FokI (rs2228570), ApaI (rs7975232), TaqI (rs731236) and BsmI (rs1544410) in 100 Jordanian volunteers (50 control and 50 Type 1 diabetes patients) was performed using the highly specific New Generation Sequencing technology.Results: The distribution of allele, genotype as well as haplotype frequencies exhibited no significant (P > 0.05) differences between type 1 diabetes patients and controls. Furthermore, no differences (P > 0.05) in the frequency of the genotypes of the Vitamin D receptor genetic variants were found in relation to the age of disease onset.Conclusion: These findings suggest these four single nucleotide polymorphisms of the Vitamin D receptor gene seem not to be associated with type 1 diabetes predisposition in Jordanian patients. Further wide genome studies are recommended to detect other genetic variant associations with type 1 diabetes among Jordanians.Keywords: jordan, diabetes, single nucleotide polymorphism, vitamin D receptor, genetic predisposition